TWO DECADES OF POLICIES FOR THE DEVELOPMENT OF THE SOUTHERN HALF OF RIO GRANDE DO SUL STATE - Antonio Paulo Cargnin (Redes, 2014)
This article aims to review the main public policies designed for the territorial division of the Southern Half of Rio Grande do Sul State in the last two decades. The analysis begins by the reasons that led to the institutionalization of this territorial division and continues by the exam of the major public policies directed to this Region, with emphasis on their instruments, results and territorial repercussions. Furthermore, the analysis envisages to identify the stakeholders who proposed these policies and how they took part in their implementation. In the analysis, a greater emphasis was given to the Program for Fostering Productive Reconversion of the Southern Half of Rio Grande do Sul State (RECONVERSUL) due to its being a concrete tool for the region’s redevelopment strategy.